The effect of liner design upon charge motion in a rotary mill - Powell, Malcolm S (Department of Mechanical Engineering, 2016)
Rotary mills are used extensively to reduce the coarse rocks of mined ores down to a product fine enough to facilitate the extraction of the valuable minerals. On the South African gold mines alone about 110 million tons of ore is mined annually, at a power cost of about R90 million, and a liner material cost of about R30 million. The charge motion in mills has been studied both theoretically and experimentally since the beginning of the century. However, a lot of the work has been purely empirical, and some of it illconceived, resulting in there still being a poor understanding of the topic. The influence of lifter-bars upon charge motion has only been considered in the past few decades, and mostly to a very limited extent. This state of affairs has left the field wide open to further research. The charge motion of an isolated rod or ball, and how it is influenced by a flat-faced lifter-bar of any face-angle and of any height, was modelled theoretically. The charge motion of rods in a glass-ended mill was filmed with a high-speed camera. The mill was fitted with a variety of lifter-bars with different face-angles and heights, and was run at a wide range of speeds. The filmed trajectories of the rods were then tracked. The coefficients of friction between the rods and lifter-bar material were measured under vibrating conditions as are found in the mill. The power draw of the mill was also measured at a wide range of mill speeds, and with lifter-bars of different heights in the mill. A good correlation between the theoretical predictions and experimental results was found over a wide range of conditions. The impact point, at which the grinding element strikes the mill shell, was considered to be of primary importance in the analysis. It was found that the height of the lifter-bar has a strong influence on charge trajectories, as the height increases from zero up to just greater than one charge radius. Thereafter the lift increases until a critical lifter-bar height is reached, beyond which the grinding element is projected off the lifter prior to reaching the tip, the height of the impact point increasing slightly and then decreasing to a constant height. However, the change in the height of the impact point is very small, so in practical terms an increase in lifter-bar height, once it is higher than the radius of the grinding element, has a very small effect upon the charge trajectories. An increase in the angle of the lifter-bars was found to have a strong influence upon the height of the charge trajectories. A linear relationship between the mill speed and the impact angle was dicovered, and changes in the mill speed strongly influence the charge trajectories. It was also found that the power draw of a mill depends on the liner configuration, with power draw decreasing as the lifter-bar height is increased. Some new and surprising effects of lifter-bar geometry upon the charge trajectories, which are of great practical importance, have been discovered. The theoretical model is an advance upon all previous models, and agrees well with experimental results over a wide range of conditions.